Tax Holiday and Foreign Direct Investment In Indonesia - Liza Herdiyati; Setyo Tri Wahyudi (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2020)
Foreign Direct Investment Inflows is important aspect of promoting economic growth and decreasing the unemployment rate. One of investment incentive applied in Indonesia is Tax Holiday. Meanwhile, research on tax holiday and their relation to foreign investment in Indonesia is still rare. This paper is aimed to measure the impact of Tax Holiday toward Foreign Direct Investment inflows in Indonesia. So, this study also compares the impact of tax holidays on 18 industries in Indonesia. The research found that the Tax Holiday incentive did not reach the expected target. Only 9 out of 18 business sectors affected by this policy, accounted for only 50% of its industrial target. The government’s role is highly expected to evaluate the target of Tax Holiday, for example giving priority and adding incentives for industrial sectors that are clearly affected by the tax holiday policy.Keywords: Foreign Direct Investment; Investment Incentive; Tax Holiday.